Dhalang Sebagai Role Model Dalam Mengembangkan Kemampuan Berbicara Bahasa Jawa Siswa SD - Dimas Saputra; Yulvia Mardlatillah; Reza Fandi Tyasari; Muhammad Nofan Zulfahmi (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Javanese language learning has an important role in preserving regional culture and identity. This research aims to examine the role of a dhalang as a role model in developing Javanese speaking skills in elementary school (SD) students. The method used in this research is descriptive qualitative using data collection techniques as well as through observation, interviews and documentation. The results of this research indicate that a dhalang can function as an inspiration and motivator for students in learning Javanese. Through an interactive wayang method full of dialogue, students can more easily understand Javanese vocabulary and sentence structures. Apart from that, the presence of dhalang in learning activities provides a pleasant learning atmosphere and strengthens students' interest in speaking Javanese more actively. This research concludes that the integration of wayang art in Javanese language learning is effective in improving elementary school students' speaking skills.